The twelve days of Dash & Lily - Cohn, Rachel; Levithan, David (Alfred A. Knopf, 2016)
Dash and Lily have had a tough year since readers first watched the couple fall in love. Lily's beloved grandfather suffered a heart attack, and his difficult road to recovery has taken a major toll on her typically sunny disposition. With only twelve days left until Christmas--Lily's favorite time of the year--Dash, Lily's brother Langston, and their closest friends take Manhattan by storm to help Lily recapture the holiday magic of New York City in December.